Ground-truthing' Chinese development finance in Africa: Field evidence from South Africa and Uganda - Edwin Muchapondwa; Daniel Nielson; Bradley Parks; Austin M. Strange; Michael J. Tierney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
A new methodology, Tracking Under-Reported Financial Flows (TUFF), allows us to systematically gather open-source information - e.g. news reports, case studies, project inventories from embassy websites, and grant and loan data published by recipient governments - about Chinese development finance activities in Africa that can be updated and improved through crowd-sourcing. In this study we create and field-test a replicable 'ground-truthing' methodology following an established protocol to verify and update existing data with in-person interviews on Chinese development finance and site visits in Uganda and South Africa. Ground-truthing generally revealed close agreement between open-source data and answers to protocol questions from informants with official roles in the Chinese-funded projects
Keywords: C80; F35; O19; O55; 330; China; aid; development finance; Africa; data collection; ground-truthing